Chitosan-Zein Nano-in-Microparticles Capable of Mediating In Vivo Transgene Expression Following Oral Delivery - Farris, Eric (J Control Release, 2017)
The oral route is an attractive delivery route for the administration of DNA-based therapeutics, specifically for applications in gene therapy and DNA vaccination. However, oral DNA delivery is complicated by the harsh and variable conditions encountered throughout gastrointestinal (GI) transit, leading to degradation of the delivery vector and DNA cargo, and subsequent inefficient delivery to target cells. In this work, we demonstrate the development and optimization of a hybrid-dual particulate delivery system consisting of two natural biomaterials, zein (ZN) and chitosan (CS), to mediate oral DNA delivery. Chitosan-Zein Nano-in-Microparticles (CS-ZN-NIMs), consisting of core Chitosan/DNA nanoparticles (CS/DNA NPs) prepared by ionic gelation with sodium tripolyphosphate (TPP), further encapsulated in ZN microparticles, were formulated using a water-in-oil emulsion (W/O). The resulting particles exhibited high CS/DNA NP loading and encapsulation within ZN microparticles. DNA release profiles in simulated gastric fluid (SGF) were improved compared to un-encapsulated CS/DNA NPs. Further, site-specific degradation of the outer ZN matrix and release of transfection competent CS/DNA NPs occurred in simulated intestinal conditions with CS/DNA NP cores successfully mediating transfection in vitro. Finally, CS-ZN-NIMs encoding GFP delivered by oral gavage in vivo induced the production of anti-GFP IgA antibodies, demonstrating in vivo transfection and expression. Together, these results demonstrate the successful formulation of CS-ZN-NIMs and their potential to improve oral gene delivery through improved protection and controlled release of DNA cargo.